The relationship between thermal performance, thermal comfort and occupants. A study of thermal indoor environment in selected students accommodation in Universiti Sains Malaysia (USM), Penang. - R S Wafi, Sulaiman (2008)

(untitled)
Thermal comfort is considered to be a principal requirement that is usually demanded of by occupants of accommodation units. A compatible indoor climate design is actually a modification of the external environmental system and is designed to provide comfort for occupants. There is a reciprocal relationship between climate and man in both indoor and outdoor areas. Thermal comfort plays a significant role in organizing that relationship and in activating it, thus making an area inhabitable and well adapted for daily existence. In this paper, the relationship between the indoor thermal comfort and the external equatorial climate of Malaysia is investigated in student accommodation quarters, in Universiti Sains Malaysia (USM).These accommodation quarters known as “hostel” would be studied for their thermal performance and energy consumption patterns. To accurately determine these aspects, data regarding the building envelope, plan, system, orientation, and operation design would be gathered. This information would be compiled from the various hostels located within the university precincts. Finally, the comfort condition of the hostels would be estimated via comfort surveys and on site measurements.